The Effect of the Brand Value on Firm Value: An Empirical Implementation on Global Brands - Volkan Topuz, Yusuf; Ak?it, Nazl? (British Journal of Marketing Studies, 2016)
The present study tested the effect of the brand value on market values of the firms traded on global scale. Within this scope, the study sample consisted of the firms included in "The Best 100 Brands" which is annually announced by Interbrand continuously for 2001 -2012. The effect of brand values of such global enterprises acting in different sectors on stock prices was tested through panel regression by considering possible lag effects. The outcomes obtained from the study showed that the brand value (current and lag effects) has a positive and statistically significant effect on stock prices.